Thrombolysis for acute ischemic stroke by tenecteplase in the emergency department of a Moroccan hospital - Ahmed Belkouch; Said Jidane; Naoufal Chouaib; Anass Elbouti; Tahir Nebhani; Rachid Sirbou; Hicham Bakkali; Lahcen Belyamani (The Pan African Medical Journal, 2015)

(untitled)
INTRODUCTION: thrombolysis has radically changed the prognosis of acute ischemic stroke. Tenecteplase is a modified form of rt-PA with greater specificity for fibrin and a longer half-life. We report the experience of a Moroccan tertiary hospital in thrombolysis using Tenecteplase. METHODS: we conducted an open prospective study of all patients who were treated with Tenecteplase for anacute ischemic stroke admitted to our emergency department. Tenecteplase was administered intravenously at a dose of 0.4 mg/kg single bolus. The primary outcome measure was the proportion of patients achieving significant early neurological recovery defined as an improvement of 4 or more points on the NIHSS score at 24h. RESULTS: 13 patients had been treated by intravenous thrombolysis. 31% were women. Mean age was 63 years old. The mean NIHSS score at admission was 14.3 and 24h after was at 9.1. The right middle cerebral arterywas involved in 69% of cases. The carotid atherosclerosis was predominant 63.3% and the cardio embolic etiology 27%. The mean time to the first medical contact after the onset of symptoms was 3h 30 min. One patient presented a capsulo-lenticular hematoma of 5 mm3 in the same side of the ischemic stroke. CONCLUSION: tenecteplase is a more interesting thrombolytic than alteplase, it seems to be more suitable for thrombolysis in our center.